A Comparative Correlation between the Oral Microbiome of Diabetes Mellitus and Healthy Individuals and their Relation with Some Demographic Parameters - Ahmed, Esraa; Mouruj. A. Alaubydi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Diabetes Mellitus (DM) is a chronic disease distributed worldwide and dominantly related to different types of diseases especially microbial infections, this study aimed to find the relationship between DM mouth microbiome and some demographic factors. Sixty saliva specimens and bacterial oral swabs were collected from randomly selected DM patients, including 29 females and 31 males enrolled in this study, which was obtained from the Al-Mustansiriya University national diabetes center in Baghdad, and other 40 apparently healthy people specimens and swabs were collected from 25 females and 15 males as a control group for the period starting November / 2021 to February / 2022. The results revealed that the most prevalent bacterial genera in the patients' group were Staphylococcus spp. 57(38.26%), Enterobacteriaceae spp. 55(36.91%), Pseudomonas spp. 13(8.72%), Streptococcus spp. and Acinetobacter spp. each was 8(5.37%), and then, Corynebacterium spp. 5(3.36%), and each Neisseria spp., and H. influenza were 2(1.34%). These percentages were significantly different from those in the control group which were Staphylococcus spp. 33(43.4%)(S. aureus 34.21% and S. epidermidis 9.22%), Enterobacteriaceae spp. 32(42.11%), Bacillus spp. 4(5.2%), Acinetobacter spp. 3(3.9%), and each Pseudomonas spp. and Streptococcus spp. were 2(2.7%). In the same context, the results showed there is no significant difference between smokers for patients /control which were  25(17%)/15(19.74%), as well as, non-smokers 105 (71.43%) / 55 (72.37%) and ex-smoking 17(11.57%)/6(7.89%) in bacterial isolates foundation in the oral cavity of DM patients and control. Acidic oral pH is the predominant pH among patients and control individuals, in spite of there being no significant differences among different oral pH levels. As well as the results revealed that gender does not affect the types of the oral microbiome.